Republic of Poland : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Republic of Poland. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that Poland's near-term growth momentum remains strong, supported by accommodative monetary and fiscal policies and sizeable European Union transfers. The economy is operating above potential, with the unemployment rate at a historical low. Growth is projected to accelerate to 3.6 percent in 2017 and remain strong in 2018. Long-term growth, however, will be more subdued, unless adverse demographics and structural constraints on investment and productivity growth are addressed. Risks to the near-term outlook are broadly balanced. Monetary policy remains accommodative, with policy rate kept at a historically low level since early 2015.